2019
DOI: 10.1128/msphere.00568-19
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Components Modulate Human Astrovirus Infectivity in Cells and Reconstituted Intestinal Tissues

Abstract: To ensure transmission, enteric viruses must maintain their infectivity during the various environmental challenges that they face in transit within and between hosts. Increased knowledge of the factors affecting enteric virus survival may help to control their transmission. This study reveals that specific fecal bacterial components preserve classic human astrovirus infectivity by stabilizing viral particles. However, the outcomes of stool-virus interactions are very variable, ranging from protection to a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 60 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…Bacterial lipopolysaccharide and peptidoglycan also enhance thermostability of Reoviruses, which in turn promotes infection of host cells following environmental stress (Berger et al, 2017). Similar virion stability and infectivity enhancement has also been observed with human Astroviruses (Perez-Rodriguez et al, 2019). This suggests that interactions between viral pathogens and the bacterial communities are likely operative at distinct host niches including the respiratory tract in addition to the better characterized synergies operative for enteric pathogens.…”
Section: Resultssupporting
confidence: 74%
“…Bacterial lipopolysaccharide and peptidoglycan also enhance thermostability of Reoviruses, which in turn promotes infection of host cells following environmental stress (Berger et al, 2017). Similar virion stability and infectivity enhancement has also been observed with human Astroviruses (Perez-Rodriguez et al, 2019). This suggests that interactions between viral pathogens and the bacterial communities are likely operative at distinct host niches including the respiratory tract in addition to the better characterized synergies operative for enteric pathogens.…”
Section: Resultssupporting
confidence: 74%
“…Bacterial lipopolysaccharide and peptidoglycan also enhance thermostability of reoviruses, which in turn promotes infection of host cells following environmental stress (17). Similar results with respect to virion stability and infectivity enhancement have also been observed with human astroviruses (22). This suggests that interactions between viral pathogens and the bacterial communities are likely operative at distinct host niches, including the respiratory tract, in addition to the better-characterized synergies operative for enteric pathogens.…”
Section: Discussionmentioning
confidence: 56%
“…As a loss in molecular detection was only observed at 35°C on day 7 and 14, these findings suggest a potential role of stool microbiota in the stability of astrovirus nucleic acid. For example, an inverse correlation between the relative abundance of the bacterial genus Blautia in stool samples and the effect of that sample on human astrovirus viability has previously been observed (12). It would be of interest to further investigate whether decreased astrovirus stability at elevated temperatures can be replicated in other stool specimens and if stability is associated with certain bacterial populations.…”
Section: Discussionmentioning
confidence: 90%
“…Few published studies have evaluated the effect of time and temperature on the molecular detection of viral enteropathogens in clinical specimens; however, a study quantifying loss of norovirus RNA RT-PCR positivity in clinical stool samples did not observe a significant change in molecular detection over 7 years of storage at refrigeration temperatures (10). Although environmental factors outside of the host can negatively impact the integrity of viral nucleic acids, the clinical matrix (stool or vomit) by which the virus is shed has shown to be protective (11,12). When we assessed stability of clinical stool specimens stored in FecalSwab samples for molecular detection, we observed that viral targets remain relatively stable across the tested temperature range up until the final time point (day 14) with the exception of human astrovirus.…”
Section: Discussionmentioning
confidence: 99%